(untitled) (Lundiana: International Journal of Biodiversity, 2002)
Patterns of biogeographical distribution of gall-forming insects are well-studied around the world. Hygrothermally and nutritionally-stressed habitats usually support rich galling insect communities. However, studies on gall diversity in the dry chaco of South America are still lacking. This study aimed to describe the insect galls found in five areas in the Central chaco in the Province of Salta, Argentina: San Domingos, Salta Florestal, Las Lajitas, and two sites at the Estación Biológica Los Colorados. Twenty-nine morphospecies of galling insects were found in the five areas sampled. They occurred on 17 host plant species that belong to 10 families. The most attacked family was the Leguminosae (8 species), which supported 52% of the chaco galling fauna (15 species). Prosopis elata, P. nigra and P. roscefalia were the most attacked species, supporting 3 galling species each. Galls were predominantly induced by Cecidomyiidae (Diptera) (62.1%), which is consistent with the patterns found elsewhere in the world. The most speciose site for galling insects was in the Estación Biológica Los Colorados (14 morphospecies in site I and 11 morphospecies in site II), probably indicating the influence of the degree of land conservation on the biodiversity of gall-forming insects.